Biological Characterizations of H5Nx Avian Influenza Viruses Embodying Different Neuraminidases - Yu, Yuandi; Zhang, Zaoyue; Li, Huanan; Wang, Xiuhui; Li, Bo; Ren, Xingxing; Zeng, Zhaoyong; Zhang, Xu; Liu, Shukai; Hu, Pingsheng; Qi, Wenbao; Liao, Ming (Frontiers in Microbiology, 2017)
The H5 subtype virus of Highly Pathogenic Avian Influenza Virus (HPAIV) has caused huge economic losses to the poultry industry and is a threat to human health. Until 2010, H5N1 subtype virus was the major genotype in China. Since 2011, reassortant H5N2, H5N6, and H5N8 viruses were identified in domestic poultry in China. The clade 2.3.4.4 H5N6 and H5N8 AIV has now spread to most of China. Clade 2.3.4.4 H5N6 virus has caused 17 human deaths. However, the prevalence, pathogenicity, and transmissibility of the distinct NA reassortment with H5 subtypes viruses (H5Nx) is unknown. We constructed five clade 2.3.4.4 reassortant H5Nx viruses that shared the same HA and six internal gene segments. The NA gene segment was replaced with N1, N2, N6, N6 (with an 11-amino acid deletion at the 58th to 68th of NA stalk region), and N8 strains respectively. The reassortant viruses with distinct NAs of clade 2.3.4.4 H5 subtype had different degrees of fitness. All reassortant H5Nx viruses formed plaques on MDCK cell monolayers, but the H5N6 grew more efficiently in mammalian and avian cells. The reassortant H5Nx viruses were more virulent in mice as compared to the H5N2 virus. The H5N6 and H5N8 reassortant viruses exhibited enhanced pathogenicity and transmissibility in chickens as compared to the H5N1 reassortant virus. We suggest that comprehensive surveillance work should be undertaken to monitor the H5Nx viruses.